Pola Tabligh Komunitas Pemuda Hijrah - Agung Muhajir, Pratama (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this research is to know how kind of activities tabligh Pemuda Hijrah community in Masjid Al-Lathiif Jalan Saninten No. 2 Bandung and find out how the pattern of tabligh Pemuda Hijrah community in doing tabligh activities. The method used in this research is descriptive method, that is the method that guides the researcher to explore or photograph the social situation which is thoroughly researched, broad and deep. The results showed that the type of activity of the Pemuda Hijrah community as a youth activity packed with Islamic values. Various activities from the start of routine studies, Qur'anic tahsin, maqomat learning, tabligh akbar, qiyamul lail and youth events are youth activities in which there are Islamic values. The results showed that the type of activity of the Pemuda Hijrah community as a youth activity packed with Islamic values. Various activities from the start of routine studies, Qur'anic tahsin, maqomat learning, tabligh akbar, qiyamul lail and youth events are youth activities in which there are Islamic values. With the aim of the Pemuda Hijrah community it can embrace all the youths back to God's way through youth activities. Ketword: Komunitas, Tabligh, Islam, Pemuda Hijrah